The Development of Caketisserie Bakery & Café Online Cake Ordering System - Lim, Yan yun; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2023)
Caketisserie Bakery & Café is a home-based bakery that accepts the booking for cakes using the instant messaging application and manages the orders using Microsoft Excel. However, this current method is inconvenient and prone to human errors. So, it may decrease work efficiency, affect the business operations and lead to dissatisfaction among customers. Therefore, this study aims to develop an online cake ordering system using web-based approach to assist in the online cake booking process. This system is developed using Waterfall model and object-oriented approach. Meanwhile, the development of this system is done by using MySQL database, PHP and HTML programming language. Generally, this system will help to enhance the efficiency in managing the orders, improve the smoothness of business operations and bring convenience to customers for ordering cakes.